Discourse, Narrative, and Voice: The Power of Communicating Bioethics Through the Media - Gallois, Hortense (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2024)
This perspective explores the role of the bioethicist in shaping public discourse through the media, while accounting for the power of narratives and voice.